Risk factors of COVID-19 vertical transmission among pregnant and non-pregnant Filipinos in Metro Manila: a multicentre cohort study protocol - Emmanuel S Baja; Zypher Jude G Regencia; Erlidia F Llamas-Clark; Rebecca B Singson; Francisco M Heralde; Mayan U Lumandas; Maria Esterlita T Villanueva-Uy; Maria Stephanie Fay S Cagayan (BMJ Open, 2022)
Introduction The novel (COVID-19 was first reported to have originated in Wuhan, China, in December 2019. This new strain, SARS‐CoV‐2, has spread rapidly worldwide, prompting the WHO to declare the COVID-19 outbreak a global pandemic. The main objective of this cohort study is to determine the risk factors of COVID-19, the modes of COVID-19 vertical transmission, and the maternal and fetal outcomes among non-pregnant and pregnant women and their fetuses.Methods and analysis This is a multicentre epidemiological study that will involve a prospective cohort. COVID-19 status among consulting non-pregnant and pregnant women in public hospitals in Manila, Philippines, will be determined and monitored for 6–12 months. Swab specimens from the nasopharynx, cervix, rectum, amniotic fluid, placenta, cord blood and breastmilk will be collected during consult and admission for reverse transcription-PCR (RT-PCR) testing. Blood will be collected during the postdelivery period to monitor the women and their neonates for any undue development and determine the antibody development to indicate an infective or non-infective state. Evidence of vertical transmission will be explored with the presence or absence of the virus using the maternal and fetal neonatal RT-PCR and lateral flow antibody status. Descriptive and inferential statistics will be done, including the associations between exposures and risk factors, description of clinical characteristics, and the COVID-19 status of the participants.Ethics and dissemination The Single Joint Research Ethics Board of the Department of Health has approved this protocol (SJREB 2020-30). The study results will be disseminated through conference presentations, peer-reviewed articles, and various stakeholder public forums and activities.